TANGGUNG JAWAB PERDATA PARA PIHAK DALAM PERDAGANGAN MELALUI SISTEM ELEKTRONIK PADA STARTUP MULTINASIONAL LAZADA DALAM PERSPEKTIF HUKUM E-COMMERCE DI INDONESIA - Clara Beatrice Pisarta; Dona Budi Kharisma (Fakultas Hukum Universitas Sebelas Maret, 2023)
This article aims to analyze the civil liability of the parties at Lazada if there is default in the online sale and purchase agreement in relation to the law of e-commerce in Indonesia. And to see the legal protection of Lazada's online buying and selling agreements with e-commerce laws in Indonesia. This research is a descriptive normative legal research. The approach used is a statue approach. The materials used in the study were selected from primary legal materials and secondary legal materials using techniques and data in the form of literature study. In analyzing legal materials and in data analysis techniques used the syllogism method. Based on the research results, there is still a lack of explanation in the electronic contracts at Lazada about civil liability and existing repressive legal protections. It is hoped that the government will provide assertiveness through good preventive legal protection and for Lazada to tidy up the class and the contents of the agreement.